Social Representations Of Diseases Linked To Climate Change In The Population Of A Slum District: A Case Study From Haiti - Ammcise Apply; Francklin Benjamin; Lucainson Raymond; Daphnée Michel; Daphenide St Louis; Evens Emmanuel (European Scientific Journal, ESJ, 2021)
Faced with the threats posed by climate change to global public health in the 21st century, the island of Haiti has a duty to inform the population and disseminate knowledge on the health consequences of the phenomenon. The effects of climate change are imminent for the country. In terms of health, the consequences will particularly accentuate the prevalence of endemic diseases, water-borne and infectious pathologies, malnutrition and undernourishment. Also, information on this issue must be widely disseminated through environmental and health education in order to raise awareness in the population and encourage them to modify their daily lifestyles through mitigation and adaptation. Previous work on strategies for popularizing scientific knowledge has shown that culture and poverty constitute obstacles to changes in behavior favoring mitigation and adaptation to climate change. The study of the Social Representations of the populations or social groups concerned makes it possible to discarded them.. From this point of view, this article questions and analyzes the social representations of vector pathologies including Malaria, Dengue, Chikungunya and Zika among the residents of Jalousie, one of the vulnerable neighborhoods of the Metropolitan Region of Port-au-Prince (MRPP - Haiti). This work highlights the link established by the population of Jalousie between climate change and the transmission of the vector-borne diseases mentioned. It does this by considering elements of Haitian popular knowledge likely to build understanding that combines the prevention and symptomatology of these pathologies with knowledge of public hygiene and supernatural phenomena. The survey carried out on a representative sample of 121 residents of the Jalousie district, a slum area of MRPP, shows that vector-borne diseases are assimilated with epidemics and their transmission due to changes in the seasons (temperature change: hot weather, rainy weather in Haiti).